Dampak Bullying dan Strategi Intervensi pada Siswa Sekolah Dasar - Farida, Eva Nur Farida; Prasetyo, Teguh; Laeli, Sobrul (EDUPEDIA Publisher, 2024)
This study investigates the phenomenon of Bullying among elementary school students, focusing on intervention strategies. Employing a qualitative approach and a case study conducted at Elementary School Pajagan during the academic year 2023/2024, the research explores the behaviors, perceptions, motivations, and actions of students who have experienced Bullying. Utilizing data analysis techniques such as data reduction, presentation, and technique triangulation, including observation, interviews, and documentation. The study highlights influential factors like family dynamics, economic conditions, peer influence, and social media engagement. The findings underscore the short-term and long-term impacts of Bullying on victims' behavior and mental health. Additionally, the article outlines teacher strategies, encompassing vigilant supervision, positive consequences, and the creation of a supportive social context. Parental strategies involve close supervision, personal guidance, and teacher collaboration to mitigate Bullying. In conclusion, this article provides comprehensive insights into strategies for addressing Bullying among elementary school students, offering valuable guidance for schools, educators, and parents in preventing and managing Bullying within educational settings.